Republic of Kazakhstan : 2018 Article IV Consultation-Press Release; and Staff Report. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2018)
Recovery is gaining strength, while inflation has been declining and the tenge has continued to float. Export growth-driven by oil, metals, and mining-has reduced the current account deficit. State support to banks led to a higher fiscal deficit in 2017, although there was underlying adjustment. The 2018 budget foresees further adjustment and ambitious spending reforms. Consolidation is set to continue over the medium term to rebuild buffers. The authorities have taken major steps to secure financial sector stability, but actions have been costly financially and risks remain. More work is needed, especially to overhaul bank business models and address gaps in supervision. Progress is being made on flagship structural reforms (business climate, governance), although, in practice, the measures taken have yet to prove their effectiveness in full. Efforts should continue to support greater productivity, inclusivity, connectivity, and diversification. Risks relate to oil prices and slower growth in key trading partners (Russia, China, EU).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet